A new cooperation spectrum sensing algorithm based on energy detection - Caimei FU; Youming LI; Guili ZHOU; Mingchen YU; Jingwen TONG; Xupeng WANG (Dianxin kexue)
To improve the reliability of spectrum sensing in cognitive radio system,a new cooperation spectrum sensing algorithm was proposed.In this algorithm,the property of the low probability between adjacent frames of the states change was used and then the decision was made by combing the energy value of the current sensing frame with that of the neighboring frame.Therefore,the proposed algorithm could decrease the miss detection probability in case of the instantaneous signal energy dropping when primary user used the licensed spectrum.Furthermore,theoretical expressions for detection probability and false alarm probability were derived.Finally,theoretical analysis and simulation results verify that the detection performance of the proposed algorithm is better than that of cooperative spectrum sensing which is based on the classical energy detection.